DEVELOPMENT OF SERUM WITH 4-N-BUTYLRESORSINOL IN THE TRANSETOSOMES VESICULAR SYSTEM - ROSMIATI, MEITI; SOPYAN, IYAN; CHAERUNISAA, ANIS YOHANA; ABDASSAH, MARLINE (International Journal of Applied Pharmaceutics, 2024)
Objective: The study aimed to develop a transetosome system as a delivery system of 4-n-Butylresorcinol (4nBR) and evaluate their physicochemical characteristics and skin penetration capacity compared with another vesicles system. Methods: Transethosomes were prepared through cold methods and the optimization of the formulation was carried out using “Box–Behnken design” approach from Design-Expert software (version 13.0. 3. 0, State-Ease Inc., Minneapolis, MN). The independent variables were soya lecithin, surfactant (Tween 80: Span 80 with a ratio of 1: 3) and Ethanol. The prepared formulations were characterized for vesicle size, polydispersity (PDI), zeta potential using a particle size analyzer and entrapment efficiency. Furthermore, transethosomes were formulated in serum preparations that tested for in vitro penetration test compared to serum with ethosomes, transfersomes and non-vesicles system. Results: Transethosomes formula optimization using box benhken approach produced a formula of 5.53 % soya lecithin, 3 % surfactant (Tween 80: Span 80 with a ratio of 1: 3) and 30 % Ethanol. The optimized formulation obtained particle size result of 197.4 nm; Polydispersity Index 0.421; zeta potential-56.8 mV and entrapment efficiency 98.40 %. Transethosomes serum met physical stability tests and in vitro penetration test showed better results compared to serum with ethosomes, transfersomes and non-vesicles system; the percentage of cumulative penetrated amounts of transethosomes serum, transfersomes, ethosomes and non-vesicle serum, respectively, was 41.43%; 23.59%, 19.85% and 2.43%. Conclusion: Development of 4nBR transethosomes using surfactant as edge activators and ethanol as an enhancers through optimization with box Behnken design resulted in transethosomes composition as ultra-deformable vesicles that fulfiled the physical characteristics, stability and permeability of 4nBR.